Application of “Tree Hole Listening” psychological support service in emotional management of neurology nurses (“树洞倾听”心理支持服务在神经内科护士情绪管理中的应用) - FEI Cailian (费才莲); WANG Yu (王瑜); ZHANG Jingyi (张静怡); XIE Juan (谢娟) (中西医结合护理)
Objective This study aimed to investigate the impact of utilizing the “Tree-Hole Listening” psychological support service on the emotional management of neurology nurses. Methods A self-controlled study was carried out from May to November 2023, involving 19 neurology nursing staff members, The intervention spanned 6 months and assessed participants' emotional management by implementing a “Tree Hole Listening” psychological support service. The Positive and Negative Affect Schedule (PANAS), Chinese Emotional Labor Scale (ELS-C). Emotional Management Ability Scale and self-made Nurse Satisfaction Assessment were employed before and after the intervention. Results The positive emotional score had increased and negative emotional score had decreased after introducing the emotional management of Tree Hole Listening psychological support service( P＜0. 01). The post-intervention score of ELS-C (46. 74 ± 7. 84) was notably lower than pre-intervention score (53. 11 ± 7. 06), with a significant difference (P＜0. 05). There was a significant improvement in nurses' ability to express emotions and a reduction in expressive suppression after intervention of the “Tree Hole Listening” psychological support service(P＜0. 05), leading to increased nursing satisfaction. Conclusion Application of' “Tree Hole Listening” psychological support service as an emotional management method could effectively regulated the psychological state of neurology nurses, resulting in decreased psychological pressure, improved emotional stability and positivity, enhanced emotional management abilities among nurses, and an increase in nurse satisfaction. (目的 探讨“树洞倾听”心理支持服务在神经内科护士情绪管理中的应用效果。方法 采取自身前后对照研究, 选取2023年5月—11月神经内科19名护理人员为研究对象, 干预时间为6个月, 以设置“树洞倾听”的方法对其情绪管理进行研究。干预前后均使用正性负性情绪研究量表(PANAS)、汉化情绪劳动量表、情绪管理能力量表、护士满意度测评。结果 实施“树洞倾听”情绪管理干预后, 神经内科19名护理人员的正性负性情绪研究量表(PANAS)正性情绪维度分值提高, 负性情绪维度分值降低, 差异有统计学意义(P＜0. 01); 干预后护士情绪劳动量表(ELQ)评分(46. 74±7. 84)分, 较干预前(53. 11±7. 06)分降低, 差异有统计学意义(P＜0. 05); 护士情绪管理量表中情绪表达维度评分较干预前提高, 情绪抑制维度评分较干预前降低, 差异有统计学意义(P＜0. 05); 护士满意度得到提高。结论 “树洞倾听”心理支持服务可有效调节神经内科护理人员的心理状态, 有利于减轻护士的心理压力, 提升护士情绪的稳定性和积极性, 提升护士的情绪管理能力, 提高护士的满意度。)